2022
DOI: 10.3390/ijerph19020933
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction and Alcohol Consumption: Empirical Evidence from China

Abstract: Despite growing attention to job satisfaction as a social determinant of alcohol-related behaviors, few studies focus on its diverse impacts on alcohol consumption. Using data from the China Family Panel Study in 2018, this study uses logistic regression analysis to examine how job satisfaction affects alcohol consumption in China, finding that people who were satisfied with their jobs were more likely to be regularly drinking. Employed people who were satisfied with their working environment and working hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In our case, factors affecting residents' trust come from five dimensions: individual factors, interpersonal factors, organizational factors, community factors, and public policy factors. This paper first controlled individual factors (gender, ethnicity, age, education, health) [20,67,68]. Second, we used the number of friends and whether respondents used the social APP WeChat as interpersonal variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…In our case, factors affecting residents' trust come from five dimensions: individual factors, interpersonal factors, organizational factors, community factors, and public policy factors. This paper first controlled individual factors (gender, ethnicity, age, education, health) [20,67,68]. Second, we used the number of friends and whether respondents used the social APP WeChat as interpersonal variables.…”
Section: Control Variablesmentioning
confidence: 99%
“…Alcohol intake has been linked to an increased risk of illness, disability, and death (7). People who were content with their working environment and working hours were more likely to routinely drink (8), as alcohol is one of the most affordable forms of addiction; this explains why alcoholism is so prevalent (9). Hierarchical multiple regression analyses indicated that gender, friends alcohol consumption, coping, and social motives for drinking were significant predictors of study participants alcohol consumption (10).…”
Section: Introductionmentioning
confidence: 99%